Outcomes assessment with two different medication administration modalities for the treatment of secondary hyperparathyroidism - Pinto,Jose Reimao (2013)
Background: The treatment of hyperparathyroidism in dialysis patients relies on adequate control of serum phosphorus (Pi) and PTH levels. Patient (pt) compliance to oral therapy at home is known to be quite poor and cannot be monitored. There is evidence that pulse (every other day) therapy with vitamin D compounds is as effective as daily administration. We hypothesized that the same might apply to calcimimetics. Objective: To assess the effect on metabolic endpoints of changing cinacalcet oral treatment from a daily, home-based administration (H), to a three-times/week witnessed administration at the end of each dialysis session in the clinic (C). Patient and methods: 93 prevalent dialysis pts in 6 clinics were included in an observational retrospective study, each patient serving as his own historical control. Inclusion criteria were: ESRD treated by haemodialysis; PTH levels > 500 ng/L and cinacalcet prescription for more than 9 months. Data was drawn from a database common to all participating clinics - EuCliDc. Blood samples were collected at the beginning of dialysis and treated at a central laboratory. Calcium (Ca), phosphorus, albumin and PTH were registered every 3 months, as well as vitamin D and cinacalcet dosages, in the last 9 months of period H and first 9 months of period C. Values during H prescription were compared with values after change to C administration through paired samples t-test. Results: We detected a significant reduction in the dose of Cinacalcet from an average dose of 1221mg/month in period H to an average dose of 674.4mg/month in period C, p < 0.0001 (95% CI 689.4 / 405.1), keeping identical dosages of Vitamin D metabolite 21.3 mic/month vs. 31.9mic/month, p=.167. This dose reduction was translated, as expected, in cost savings, going from an average Cinacalcet cost of 256/month/pt to 137.6/month/patient, p < 0.0001. PTH was more elevated in the C group 903.5 vs. 807.9ng/L, < 0.028, phosphate levels were identical, 5.0 in period H and 4.8mg/dl in period C, p = 0.065. Conclusion: Administration of Cinacalcet under supervision 3 times per week, post -dialysis, was shown to be safe, guarantees compliance and saved considerable resources for the same therapeutic efficacy.